1984
DOI: 10.1148/radiology.152.2.6739808
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic evaluation of the renal parenchyma in infancy and childhood.

Abstract: The authors evaluated 46 patients several hours to 10 years of age and found that in neonates and young infants, the renal cortex is normally as echogenic as the hepatic parenchyma. Within 2 to 3 months, the renal cortex becomes progressively less echogenic than the liver; however, in patients with renal parenchymal disease, cortical echogenicity increases. Sonography is very sensitive to this condition, especially in older children; however, the overall findings are nonspecific. The authors conclude that ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
5

Year Published

1986
1986
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 0 publications
1
20
0
5
Order By: Relevance
“…None of these patients had a history of renal disease, nor did they develop a renal disorder after one year follow-up. Because previous articles [3,5] have shown that in healthy pediatric subjects (neonates and infants excluded) echogenicity of the renal parenchyma is not increased, we believe that hyperechogenicity of renal parenchyma can be a nonspecific finding, a sign of (abdominal) illness varying from appendicitis to ileocecitis, infectious gastroenteritis or otherwise, rather than an indicator of renal disease. Only one study reported that renal echogenicity equal to the liver parenchyma is a nonspecific finding and does not suggest renal disease; that study, however, included only adults [10].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…None of these patients had a history of renal disease, nor did they develop a renal disorder after one year follow-up. Because previous articles [3,5] have shown that in healthy pediatric subjects (neonates and infants excluded) echogenicity of the renal parenchyma is not increased, we believe that hyperechogenicity of renal parenchyma can be a nonspecific finding, a sign of (abdominal) illness varying from appendicitis to ileocecitis, infectious gastroenteritis or otherwise, rather than an indicator of renal disease. Only one study reported that renal echogenicity equal to the liver parenchyma is a nonspecific finding and does not suggest renal disease; that study, however, included only adults [10].…”
Section: Discussionmentioning
confidence: 77%
“…Increased renal echogenicity of infants changes gradually in the adult pattern [7]. Several reports have stated that increased echogenicity of the renal parenchyma is an indicator of renal disease [3,4]. However, we have encountered increased echogenicity in patients with various abdominal diseases but no concurrent renal disease.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…It has been noted in intrauterine growth-retarded fetuses, presumably as a result of the associated hyperechogenicity. In transient hyperechogenic cases, the cause is transient renal insufficiency [3,10,16,17]. Increased echogenicity may represent a tubular blockage caused by Tamm-Horsfall protein precipitation [18].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperechogenic medullae were diagnosed when the fetal renal medullae displayed an echogenicity similar to that of the surrounding bone, but higher than that of the liver or spleen [10].…”
Section: Methodsmentioning
confidence: 99%